Medida da capacidade anaeróbica em atletas dos esportes coletivos de invasão : MAOD e Line Drill Test - Porto, Obanshe Severo D Acelino e (2015)
The anaerobic capacity is crutial to the results of team invasion games and can be assessed through the Line Drill Test (LDT), which shows correlations with Wingate. Its results and execution time is commonly obtained using manual timers. The anaerobic capacity can also be measured by the Maximal Accumulated Oxygen Deficit (MAOD), adopted as the gold standard for this capability. The classic version of this method requires time and cost relatively high, while the alternate version (MAODALT), although, although it presents time and execution costs reduced, has been validated exclusively for the cycle ergometer, which does not meet the motor demands of team invasion games. Based on that, three studies were developed, with the following objectives: a) Determine the reliability of results records of LDT runtime through stopwatches and video analysis; b) Validate the protocol for determining the MAOD through MAODALT, performed with treadmill in athletes of team invasion games; c) Validate the LDT as a measure of anaerobic capacity in collective team invasion games, comparing it to a gold standard test and specific to movement. Participated in the present research university basketball athletes, handball and futsal. There was good agreement between the runtime registration measures for all measures and there was no significant difference (p = 0.999). The MAODALT showed high correlation (r = 0.76; p = 0.030) and good agreement with the MAOD. Finally, MAOD obtained in the LDT (MAODLD) showed good agreement with the classic MAOD and MAODALT. Our results suggest that: a) the use of both timers and videos to record the LDT time is valid and reliable; b) The MAODALT obtained in tests on the treadmill proved to be able to estimate the classic MAOD in athletes of team invasion games; c) The LDT can be used to estimate the MAOD, however, its running time is not associated with the measure of anaerobic capacity represented by MAOD.